Essential guide to acute care - Cooper, Nicola; Forrest, Kirsty; Cramp, Paul; Patel, Rakesh (United Kingdom Wiley Blackwell, 2021)
"'...in the beginning of the malady it is easy to cure but difficult to detect, but in the course of time, not having been either detected or treated...it becomes easy to detect but difficult to cure.' Niccolo Machiavelli, The Prince It's almost 15 years since the publication of the 2nd edition of Essential Guide to Acute Care and a few more since one of the authors (NC) asked her boss at the time (PC) and a friend (KF) to help her write a book on 'everything you need to know but no-one told you' about the care of acutely ill adults. In that time it has been a best-selling book used by doctors in training, critical care outreach teams, nurses and allied health professionals working in acute areas, medical students and clinical teachers. Many things have changed since the 2nd edition: new oxygen guidelines, updated practices in fluid balance and volume resuscitation, new definitions of sepsis, and 'acute kidney injury' instead of 'renal failure' among others. This edition has been extensively re-written and updated, including a new author (RP), but we have done our best to retain the informal, easy-to-read style that made this book so popular with readers"--
Includes bibliographical references and index.
Keywords: Critical Care